Patrones, modelos y similitud de la distribución espacial de Iryanthera spp (Myristicaceae) en el Neotrópico - Zarate Gomez, Ricardo (2022)
The study of the distribution of the species is important as basic information for contribution in its conservation, for which in the present work the objectives were: to determine the patterns of distribution, to elaborate the spatial models of distribution and to evaluate the difference of the distribution of the 22 species of Iryanthera in the Neotropics (from southern Costa Rica to northern Bolivia); as a null hypothesis it was proposed that the distribution of the Iryanthera species were equal. The distribution patterns of the Iryanthera species were carried out with the exploratory data analysis with the nearest neighbor test; species distribution models were made with the maximum entropy model in the Maxent program; and the similarity of the distribution of the species was elaborated with the Bray-Curtis similarity cluster analysis with Wardis union and the similarity analysis (ANOSIM). The data source corresponded to 5161 individuals found in the herbaria AMAZ, HH, MOL, USM (Peru), INPA (Brazil), COL and HUA (Colombia); information on the internet of herbaria; sampling in the Peruvian Amazon forest; and scientific publications. Almost all Iryanthera species have the clustered distribution pattern (81.8%, p-value <0.001). Species distribution models present five types: 1. Species that are distributed only in the Caribbean. 2.- The species that are distributed approximately towards the center of the Amazon. 3.- The species are distributed in the central west of the Amazon. 4.- Species that are widely distributed in the Amazon. And 5. The species that is distributed towards the extreme East of the Amazon. Several species have different distribution patterns and others are the same, so the null hypothesis is rejected.